HeartWare left ventricular assist device for the treatment of advanced heart failure. (January 2016) - Hanke, Jasmin S; Rojas, Sebastian V; Avsar, Murat; Bara, Christoph; Ismail, Issam; Haverich, Axel; Schmitto, Jan D
The importance of mechanical circulatory support in the therapy of advanced heart failure is steadily growing. The rapid developments in the field of mechanical support are characterized by continuous miniaturization and enhanced performance of the assist devices, providing increased pump durability and prolonged patient survival. The HeartWare left ventricular assist device system (HeartWare Inc., Framingham, MA, USA) is a mechanical ventricular assist device with over 8000 implantations worldwide. Compared with other available assist devices it is smaller in size and used in a broad range of patients. The possibility of minimally invasive procedures is one of the major benefits of the device – allowing implants and explants, as well as exchanges of the device with reduced surgical impact. We present here a review of the existing literature on the treatment of advanced heart failure using the HeartWare left ventricular assist device system.